2020
DOI: 10.1101/2020.12.23.423975
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

FAM72A antagonizes UNG2 to promote mutagenic uracil repair during antibody maturation

Abstract: Activation-induced cytidine deaminase (AID) catalyzes the deamination of deoxycytidines within Immunoglobulin (Ig) genes to induce somatic hypermutation (SHM) and class switch recombination (CSR). AID-induced deoxyuracils within Ig loci are recognized and processed by subverted base excision and mismatch repair pathways that ensure a mutagenic outcome in B lymphocytes. However, it is unclear why DNA repair pathways that remove deoxyuracil from DNA are not efficient at faithfully repairing AID-induced lesions. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The trend for increased transition mutations at highly mutating AID hotspots mediated by UNG2 had previously been observed in experiments using 3T3 (mouse fibroblast) cells (Pérez-Durán et al, 2012), although the particular bias against C:G>A:T transversions was not apparent. Previous work has also shown that UNG2 is cell-cycle regulated, possibly mediated by FAM72A (Feng et al, 2020), and active primarily during G1 (Sharbeen et al, 2012). Although AID is also primarily active during G1, it may sometimes persist for slightly longer than UNG2 and thus highly targeted sites may avoid BER especially when the mutations occur just before the cell enters S phase, which would lead to fixation of C>T transitions via replication bypass.…”
Section: Discussionmentioning
confidence: 99%
“…The trend for increased transition mutations at highly mutating AID hotspots mediated by UNG2 had previously been observed in experiments using 3T3 (mouse fibroblast) cells (Pérez-Durán et al, 2012), although the particular bias against C:G>A:T transversions was not apparent. Previous work has also shown that UNG2 is cell-cycle regulated, possibly mediated by FAM72A (Feng et al, 2020), and active primarily during G1 (Sharbeen et al, 2012). Although AID is also primarily active during G1, it may sometimes persist for slightly longer than UNG2 and thus highly targeted sites may avoid BER especially when the mutations occur just before the cell enters S phase, which would lead to fixation of C>T transitions via replication bypass.…”
Section: Discussionmentioning
confidence: 99%
“…Under pathophysiological conditions, FAM72A is also expressed in various proliferating cancer cells [ 24 , 25 ]. Notably, FAM72A interacts with UNG2 [ 26 , 27 ]. This denotes that the cellular role of FAM72A is as a cooperative partner for genomic BER in order to ensure genome integrity and impede the formation of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Recent data show that decreased levels of FAM72A lead to hyperphysiological UNG2 levels, an increased uracil correction, and, thus, error-free DNA repair. In contrast, the binding of FAM72A with UNG2 antagonizes UNG2 activity and causes UNG2 degradation in B cells, leading to increased levels of genome-wide deoxyuracils and, therefore, mediating increased levels of U•G mispairs that engage in mutagenic mismatch repair, promoting the error-prone processing of activation-induced cytidine deaminase (AID)-induced deoxyuracils [ 27 , 28 ]. Thus, FAM72A bridges BER and mismatch repair in order to modulate antibody diversification during B cell and antibody maturation [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations